INNOPEDA® - pedagogia da inovação: configuração de proposta de produção textual para alunos do quinto ano do ensino fundamental – anos iniciais - Pereira, Fernanda Marisa (2022)
This is the result of an intervention project that is configured as a proposal of textual production for students of the fifth year of elementary school, based on the pillars and competences of the Finnish Teaching Strategy - INNOPEDA® - The Pedagogy of Innovation. The motivation for carrying out this work is justified by the fact that I taught in a teaching unit that adopts such a strategy, in which the research was carried out. To teach along the lines of Innopeda®, I participated in a one-year training course, and received certification from the University of Turku, Finland. Thus, the general objective of this work is to develop a didactic proposal for textual production based on the Innopeda® Teaching Strategy as a way of scrutinizing the contributions of innovation pedagogy to improve work with textual production and evaluation of textual production of students from the fifth year of Elementary School – early years. As specific objectives, I sought to investigate the application of Finnish strategy methods, such as active learning, practical activities, dialogue, interaction for the development of work with textual production and evaluation of textual production, starting from the reading of a literary book. In addition to these specific objectives, I also sought to identify the acquired skills mobilized by the application of such methods. I tried to prove the contributions of this Finnish strategy for the improvement of the work with textual production and textual evaluation of students of the fifth year of elementary school. To compose the studies on the configuration of the proposal of textual production, this text deals with future competences that are intended to be achieved in students; as well as on the importance of school planning that includes reading and textual production. In order to trace the theoretical-methodological itinerary, information from scientific publications by several authors from the Turku University of Applied Sciences (TUAS) was combined, made available on the Innopeda® website; with which other authors such as: Geraldi (1996, 2006, 2104), Koch and Elias (2015), Rojo (2019) and Marcuschi (2008, 2010, 2012), Kleiman (2002), Cosson (2009, 2014), Bordini and Aguiar (1993), Dolz and Schneuwly (2004), Figueiredo (2002), Cagliari (2009) and the National Curricular Common Base – the BNCC (2018).